P(x) is a polynomial.

Assume that P(x) is a combination of two factors

then P(x)= f(x) *g(x)

now we know that P(r)= 0, then r is a root to p(x)

then, P(x) = (x-r) g(x)

then (x-r)= p(x)/g(x) where g(x) is a factor

then (x-r) is a factor of P(x)

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

P(x) is a polynomial.

Assume that P(x) is a combination of two factors

then P(x)= f(x) *g(x)

now we know that P(r)= 0, then r is a root to p(x)

then, P(x) = (x-r) g(x)

then (x-r)= p(x)/g(x) where g(x) is a factor

then (x-r) is a factor of P(x)